Region‐specific rapid regulation of aromatase activity in zebra finch brain. Issue 6 (14th January 2016) - Comito, Devon; Pradhan, Devaleena S.; Karleen, Branden J.; Schlinger, Barney A.
Abstract : Aromatase activity in male and female zebra finch hippocampus, hypothalamus, and caudomedial nidopallium is rapidly regulated by Ca 2+ ‐dependent phosphorylation. Low ATP and Mg 2+ decrease activity, whereas nicotinamide adenine dinucleotide phosphate (NADPH), high ATP, and inhibition of protein kinase C increase activity. Evidence suggests this may occur at the synapse. These results provide a mechanism for rapid regulation of behavior via brain estrogen synthesis. Abstract: Recent studies demonstrate that rapid modulation of the estrogen synthetic enzyme aromatase, regulates hypothalamic (HYP) estrogen production, and subsequent neurophysiology and reproductive behavior. In songbirds, in addition to expression in the HYP, aromatase is expressed at high levels in several brain regions notably in the hippocampus (HP) and caudomedial nidopallium (NCM), where estrogens affect learning and memory and auditory processing, respectively. Previous studies, largely in quail HYP, show that aromatase activity is acutely down‐regulated by Ca 2+ ‐dependent phosphorylation. Here, using zebra finches ( Taeniopygia guttata ), we ask if similar mechanisms are at work in the songbird HYP and if there are sex as well as regional differences in aromatase modulation. Using in vitro assays to measure activity in homogenates or in partially purified supernatants containing microsomes and synaptosomes of the HP, HYP, and NCM, we examined effects of Ca 2+, Mg 2+, ATP, NADPH, and an inhibitor of kinase activity. We report a rapid down‐regulation of aromatase activity in the presence of phosphorylating conditions across all three brain regions and both sexes. However, regional differences were seen in response to some phosphorylating factors, some of which were improved by partial purification of the homogenates. Furthermore, while low concentrations of ATP inhibited aromatase activity, unexpectedly, inhibition was no longer seen with high ATP concentrations. These results provide evidence for a regional and temporal specificity in the rapid modulation of aromatase activity that may bear on local neuroendocrine function. Aromatase activity in male and female zebra finch hippocampus, hypothalamus, and caudomedial nidopallium is rapidly regulated by Ca 2+ ‐dependent phosphorylation. Low ATP and Mg 2+ decrease activity, whereas nicotinamide adenine dinucleotide phosphate (NADPH), high ATP, and inhibition of protein kinase C increase activity. Evidence suggests this may occur at the synapse. These results provide a mechanism for rapid regulation of behavior via brain estrogen synthesis.